The effect of phospholipids on anaphylactic histamine release - Mongar, J. L. (1972)
1. Histamine release by antigen from three sensitized rat tissues is potentiated by phosphatidyl serine (PS). The effect is greatest with isolated peritoneal cells. Phosphatidyl inositol, ethanolamine, choline and phosphatidic acid are inactive. 2. PS greatly increases the rate of antigen-induced histamine release and only slightly prolongs the duration of the release process. 3. PS shows a concentration-dependent effect over the range 1-10 μg/ml. At 10 μg/ml it is active over a wide range of antigen concentrations. 4. Calcium ions are necessary for the potentiation by PS of antigen-induced histamine release from rat peritoneal cells.